Measuring the Effectiveness of a Communication - Cooper, Charles W. (Review of religious research, 1973)
The author here presents a simple method of testing the effectiveness of a communication using a simulated pretest-posttest design. In the particular communication package studied, the intent was to effect an increase in knowledge of local pastors about the denomination's program in behalf of racial justice, to motivate them to greater personal participation in the struggle for racial justice, and to spur their congregations to a greater participation in the "Neighbors in Need" all-church offering designated for this cause. While the author found a significant gain in information following introduction of the communications package, he found no significant difference in behavior--as measured by personal participation of pastors in the struggle for racial justice, individual contributions of pastors to the "Neighbors in Need" offering, and influence of pastors upon their congregations to contribute to this offering.